2016
DOI: 10.1002/jip.1457
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Victim Resistance Strategies against Stranger Child Abduction: An Analysis of Attempted and Completed Cases

Abstract: Existing research, policy information, and materials intended to teach child safety assumes that certain behaviours will protect children in the event that a stranger tries to abduct them. However, there is little empirical basis for these assumptions. This paper examines the effectiveness of strategies thought to increase the likelihood that a child will be able to resist an attempted stranger child abduction event. Seventy‐eight cases of stranger child abduction that occurred in the UK between 1988 and 2014,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…This was confirmed by the results, which produced varying profiles between attempted and completed cases. This indicates that future studies of SCA should continue examining attempted and completed cases of SCA separately, as suggested by Newiss and Fairbrother (2004) and by Collie & Shalev Greene, 2017, 2016a, 2016b. At the simplest level, this approach has been useful as it goes beyond highlighting which individual strategies are used by offenders in SCA, but it also highlights which particular single strategies result in the poorest outcomes for victims.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This was confirmed by the results, which produced varying profiles between attempted and completed cases. This indicates that future studies of SCA should continue examining attempted and completed cases of SCA separately, as suggested by Newiss and Fairbrother (2004) and by Collie & Shalev Greene, 2017, 2016a, 2016b. At the simplest level, this approach has been useful as it goes beyond highlighting which individual strategies are used by offenders in SCA, but it also highlights which particular single strategies result in the poorest outcomes for victims.…”
Section: Discussionmentioning
confidence: 99%
“…The bulk of this literature is aimed at evaluating training programs aimed at equipping children with skills to recognise, understand, and defend themselves against a variety of offences, including SCA (see, e.g., Moran et al, 1997;Johnson et al, 2006). This research ascertains how well children will actually utilise acquired skills when faced with abduction, with other research (e.g., Collie & Greene, 2017, 2016a finding that resistance by victims can significantly impact on case outcome. It is not suggested that training children can eliminate the risk of SCA nor that onus should be placed on victims; however, this has been shown to be a potential area where resilience can be built.…”
Section: Discussionmentioning
confidence: 99%